Uji Coba Proses Pengempukan Daging dengan Ekstrak Daun Pepaya dan Ekstrak Nanas - Antonius Rizki Krisnadi (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2019)
Papaya leaves and pineapple fruit help the process of natural meat refinement. The aim of the study was to determine meat deflation with papaya leaf extract and pineapple fruit with texture of meat tenderness, aroma of meat specificity after and physical quality of meat before processing. This study uses an experimental method to look for the effect of treatment on others in controlled conditions. Using a sample of 15 expert panelists for the results of meat treatment using the categorization method. The results of the study used papaya leaf extract and pineapple fruit, that soaking for 45 minutes meat (P3) caused a change in the texture of tenderness of the meat, the aroma of the peculiarities of the meat after processing changed with the aroma of papaya leaves and pineapple fruit. While the physical quality of the meat prior to processing, the panelists gave the answer P1, which was soaking for 15 minutes. P2 and P3 in physical quality look pale and not fresh before processing. Suggestions researchers conducted further research on nutrition and water content in meat.